The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.3354/cr025205
|View full text |Cite
|
Sign up to set email alerts
|

Baltic Sea climate: 200 yr of data on air temperature, sea level variation, ice cover, and atmospheric circulation

Abstract: Relevant observed time series for the Baltic Sea region from the last 2 centuries were used to investigate climate variations and trends. These time series were: Stockholm air temperature and magnitude of seasonal temperature cycle, Stockholm sea level data, Baltic Sea maximum ice cover, and circulation types based on regional air pressure data. The definition of climate was analysed by considering how each parameter varies with the time scale. We found that 90% of the variance was for time scales shorter than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 29 publications
6
60
0
Order By: Relevance
“…This is consistent with the observed upward trend in the NAO index (Hurrell and Folland 2002) and circulation changes as reported by Jacobeit et al (2003). Eriksson et al (2007) and Eriksson (2009) extended the analysis of Omstedt et al (2004) by examining the covariability of long time series from the Baltic Sea region over different timescales during boreal winter. Over a period of 500 years, 15 periods with a clearly distinct climatic signature with respect to circulation patterns, inter-annual variability and the severity of winters were identified (see Chap.…”
Section: Long-term Circulation Changessupporting
confidence: 71%
See 3 more Smart Citations
“…This is consistent with the observed upward trend in the NAO index (Hurrell and Folland 2002) and circulation changes as reported by Jacobeit et al (2003). Eriksson et al (2007) and Eriksson (2009) extended the analysis of Omstedt et al (2004) by examining the covariability of long time series from the Baltic Sea region over different timescales during boreal winter. Over a period of 500 years, 15 periods with a clearly distinct climatic signature with respect to circulation patterns, inter-annual variability and the severity of winters were identified (see Chap.…”
Section: Long-term Circulation Changessupporting
confidence: 71%
“…As the discrepancy in 20CR compared to other reconstructions reduces in parallel to the increase in number of stations, increasing storminess with time could be an artefact due to the changing station density (Krueger et al 2013) (Higgins 1933) and severe storm analysis by Lamb and Frydendahl (1991). Furthermore, Omstedt et al (2004) found an unusually high frequency of cyclonic circulation at the end of the nineteenth century with a pronounced peak in cyclonic weather types in 1871-1885 relative to 1800-2000. According to historical weather records of gale days for Scotland, remarkably high values were recorded for 1884-1900 (Dawson et al 2002) which contrasts with very low storm activity in the 1880s derived from the 20CR model data.…”
Section: Potential Inconsistencies In Long-term Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar result has been obtained by Omstedt et al (2004). They argued that it is rather problematic to clearly define 'trends' or 'regime shifts' on shorter time scales because the Baltic Sea has decadal climate modes on the order of 30-60 years.…”
Section: Introductionsupporting
confidence: 75%